Selected ion flow tube mass spectrometry analyses of isobaric compounds methanol and hydrazine in humid air - Shestivska, Violetta; Kolivoška, Viliam; Kubišta, Jiří; Smith, David; Španěl, Patrik (Rapid communications in mass spectrometry, 2020)
RATIONALE: The volatile compounds generated by the electrochemical reduction of atmospheric carbon dioxide and nitrogen include isobaric methanol (CH3 OH) and, potentially, hydrazine (N2 H4 ). To achieve quantification of hydrazine molecules by selected ion flow tube mass spectrometry (SIFT-MS), its reactions with H3 O+ , NO+ and O2 + reagent ions must be understood. METHODS: A SIFT study (using a SIFT-MS instrument) was carried out to obtain rate coefficients and product ions for the reactions of H3 O+ , NO+ and O2 + reagent ions with N2 H4 and CH3 OH molecules present in the humid headspace of their aqueous solutions. Using the kinetics data obtained, solution headspace concentrations were determined for both compounds as a function of their liquid-phase concentrations at 10, 20 and 35°C. RESULTS: Both compounds react with H3 O+ ions via rapid proton transfer to produce CH3 OH2 + and H5 N2 + ions with the common m/z value of 33. It is revealed that NO+ rapidly transfers charge to N2 H4 (rate coefficient k = 2.3 × 10-9 cm3 s-1 ) but only slowly associates with CH3 OH (k2eff = 7.1 × 10-11 cm3 s-1 ). Thus, selective analysis can be achieved using both H3 O+ and NO+ reagent ions. The headspace methanol vapour concentration was found to increase with increasing solution temperature, but that of hydrazine decreased with an associated increase of ammonia (NH3 ) as measured with O2 + reagent ions. CONCLUSIONS: The isobaric compounds methanol and hydrazine can be separately analysed in real time by SIFT-MS using H3 O+ and NO+ reagent ions, even when they co-occur in humid air. The evolution of hydrazine from aqueous solutions can be quantitatively monitored together with its decomposition at elevated temperatures.